2021
DOI: 10.14238/pi61.6.2021.322-7
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-lymphocyte ratio and sepsis outcome in children

Abstract: Background Sepsis is the most common cause of death in infants and children worldwide. Identification of patients with a high risk of death and accurately anticipating outcomes in the early phase is very important in order to provide adequate intervention to the patient. Predictors and scoring systems have been used to determine the prognosis of sepsis n children. The platelet-lymphocyte ratio (PLR), a newly-used marker for inflammation, has received recent attention, as it can act as an indicator in a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Among the 16 included studies, nine studies had prospective designs. Studies were conducted in China ( n = 4) [ 12 , 22 – 24 ], Indonesia ( n = 3) [ 16 , 19 , 20 ], Turkey ( n = 3) [ 10 , 11 , 18 ], Iran ( n = 1) [ 14 ], Serbia ( n = 1) [ 13 ], Saudi Arabia ( n = 1) [ 9 ], Poland ( n = 1) [ 17 ], Korea ( n = 1) [ 15 ], and India ( n = 1) [ 21 ]. Seven studies reported one-month mortality [ 9 , 10 , 12 , 15 , 19 , 21 , 24 ], three studies reported in-hospital mortality [ 13 , 14 , 22 ], and one study investigated ICU mortality [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 16 included studies, nine studies had prospective designs. Studies were conducted in China ( n = 4) [ 12 , 22 – 24 ], Indonesia ( n = 3) [ 16 , 19 , 20 ], Turkey ( n = 3) [ 10 , 11 , 18 ], Iran ( n = 1) [ 14 ], Serbia ( n = 1) [ 13 ], Saudi Arabia ( n = 1) [ 9 ], Poland ( n = 1) [ 17 ], Korea ( n = 1) [ 15 ], and India ( n = 1) [ 21 ]. Seven studies reported one-month mortality [ 9 , 10 , 12 , 15 , 19 , 21 , 24 ], three studies reported in-hospital mortality [ 13 , 14 , 22 ], and one study investigated ICU mortality [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported one-month mortality [ 9 , 10 , 12 , 15 , 19 , 21 , 24 ], three studies reported in-hospital mortality [ 13 , 14 , 22 ], and one study investigated ICU mortality [ 17 ]. Five studies did not report any data in this regard [ 11 , 16 , 18 , 20 , 23 ]. The population in the two studies was septic children [ 16 , 20 ] and in 14 studies were adult septic patients [ 9 15 , 17 – 19 , 21 – 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations